A rare trauma-associated cause of central retinal vein occlusion in a young subject - Mouinga Abayi, D A; Giraud, J-M; Fenolland, J-R; El Asri, F; Sendon, D; May, F; Renard, J-P (Journal francais d'ophtalmologie, 2012)
Retinal vein occlusions are the second leading cause of retinal vascular disease, after diabetic retinopathy. In the case of young subjects, a thorough etiological investigation must be conducted in order to diagnose rare etiologies, such as this heterozygous mutation of the factor II gene associated with a central retinal vein occlusion (CRVO), occurring in a young subject within the context of trauma. The case deals with a 35-year-old soldier on a mission in a conflict zone. He was the victim of blast injury as a result of the explosion of an improvised explosive device (IED) or homemade bomb, and presented a sudden decline in visual acuity in his left eye associated with the clinical picture of a CRVO. Analysis showed a heterozygous factor II G20210A gene mutation. Retinal vein occlusions are always serious visual events. In the case of young subjects, a thorough etiological investigation must be conducted in search of rare abnormalities likely to lead to retinal vein occlusion.